PENERAPAN PEMBELAJARAN MATEMATIKA "ASIK" SELAMA PANDEMI COVID BAGI ANAK ASUH YAYASAN ANAK BANTUAN ANAK INDONESIA - Susilawati, M.; Nilakusmawati, D.P.E.; Suciptawati, N.L.P.; Tastrawati, N.K.T. (Buletin Udayana Mengabdi; Vol 23 No 6 (2024): Buletin Udayana Mengabdi, 2024)
Anak Bantuan Anak Indonesia foundation was established in 2005 with the aim of helping children from underprivileged families to stay in school up to university level. This service activity is carried out by applying "Fun" mathematics learning, aiming to be able to help students who are indeed lacking in online learning infrastructure to better understand mathematical concepts. There are 10 elementary school students and 12 junior high school students, whose activities will be carried out in two stages. The first activity is for elementary school students in the morning, and in the afternoon for junior high school students. This is done to avoid crowds to avoid infection with the corona virus. The learning theme taken is markets. For elementary school students, students are only told to buy one type of each item for several items, while for junior high school students students are told to buy more than one type for several items. The results of this activity show that students' enthusiasm is very high in playing and learning mathematics. Learning while playing the market makes students no longer feel pressured to learn mathematics, which has been the most frightening and boring subject so far. Keywords: Foster children, Markets, Online learning, Fun math learning, Indonesian Children's Assistance Foundation